2017
DOI: 10.1001/jamaneurol.2017.0666
|View full text |Cite
|
Sign up to set email alerts
|

Complex and Dynamic Chromosomal Rearrangements in a Family With Seemingly Non-Mendelian Inheritance of Dopa-Responsive Dystonia

Abstract: IMPORTANCE Chromosomal rearrangements are increasingly recognized to underlie neurologic disorders and are often accompanied by additional clinical signs beyond the gene-specific phenotypic spectrum. OBJECTIVE To elucidate the causal genetic variant in a large US family with co-occurrence of dopa-responsive dystonia as well as skeletal and eye abnormalities (ie, ptosis, myopia, and retina detachment). DESIGN, SETTING, AND PARTICIPANTS We examined 10 members of a family, including 5 patients with dopa-responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Whole-genome sequencing (WGS) studies have shown that cxSVs are considerably more abundant and diverse than had been previously appreciated, representing an estimated 2% of the SVs in the human genome, and each human genome contains on average 14 cxSVs [ 11 ]. The presence of multiple types of cxSVs has also been independently observed in several other studies [ 5 , 12 14 ]. Extreme cases of cxSVs, such as chromothripsis, have also been identified in both cancer cells and the germline and involve hundreds of rearrangements often concerning more than one chromosome [ 11 , 15 ].…”
Section: Introductionsupporting
confidence: 73%
“…Whole-genome sequencing (WGS) studies have shown that cxSVs are considerably more abundant and diverse than had been previously appreciated, representing an estimated 2% of the SVs in the human genome, and each human genome contains on average 14 cxSVs [ 11 ]. The presence of multiple types of cxSVs has also been independently observed in several other studies [ 5 , 12 14 ]. Extreme cases of cxSVs, such as chromothripsis, have also been identified in both cancer cells and the germline and involve hundreds of rearrangements often concerning more than one chromosome [ 11 , 15 ].…”
Section: Introductionsupporting
confidence: 73%
“…The rearrangements can include deletions, insertions, and inversions of one or more trangene sequences . A similar chromothripsis of human genomes occurs in autism and related neurodevelopmental disorders, suggesting that structural alterations in the genome can alter neuronal function Lohmann et al, 2017;Talkowski et al, 2012). We wondered whether a similar complex genetic rearrangement occurred in Nd1 and Nd2 transgenes leading to a toxic gain-of-function.…”
Section: Neurodegenerationmentioning
confidence: 99%
“…In addition, several individuals were reported to have delayed motor milestones. Interestingly, subjects 2 and 3 both had deletions involving the GCH1 gene, which was recently implicated in disease in a family with autosomal dominant or recessive doparesponsive dystonia in addition to eye and skeletal anomalies attributed to BMP4 haploinsufficiency [15]. However, dystonia was not reported in either of the newly reported cases described in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Overall, only a few studies have been published examining the phenotypic spectrum associated with BMP4 deletions and loss-of-function variants. Recently, a large family with dopa-responsive dystonia, eye, and skeletal anomalies was reported with a complex chromosomal rearrangement involving at 14q21q22, which resulted in the deletion of BMP4 and GTP cyclohydrolase 1 (GCH1, MIM# 600225); deletion of these genes could independently explain the complex phenotype and inheritance pattern observed in this family [15]. Several new studies have also emphasized the importance of considering multiple, independent molecular diagnoses in subjects with atypical or 'expanded' phenotypes [16].…”
Section: Introductionmentioning
confidence: 95%